Slavery, Nationality and “Political Half-Breeds” - Uemori, Celso (Pontifícia Universidade Católica de São Paulo, 2004)
This article deals with the following themes: the influence of slavery on the constitutionof Brazilian society; the abolition of slavery and the concessions of liberty asinstruments capable of extirpating the “original evils” produced by the social system ofservitude; and the effects of this system on the creation of what Joaquim Nabucotermed “the political half-breeds” or, in other words, the coexistence in the Brazilianmindset of the authoritarianism of the master and the submissiveness of the slave.